(untitled) (Journal of Management and Social Sciences, 2021)
Education is widely acknowledged as a key agent of economic growth and a vital instrument for supporting sustainable development. However, in recent times, the sector has suffered an extensive decay in Nigeria. This paper seeks to examine the major causes of the decay, the effects of the decay in the educational sector and the role of stakeholders in maintaining high standard in the sector. To achieve this goal, the paper utilizes secondary sources and classical theory is adopted as a theoretical lens to guide the study. The study finds that corruption, insecurity, poor funding and decline of the teaching profession are among the major factors responsible for the recent fall off in education. The paper also finds that the most conspicuous indication of the lost era of educational excellence in Nigeria is the abysmal quality of the student intake. Consequently, the educational standard has deteriorated and this has created increasing rate of illiteracy, poverty and underdevelopment among other effects. The paper concludes that there is a need for synergy among the stakeholders with a view to putting in place viable measures to deal with the embarrassing and insidious menace in Nigeria. The paper, therefore, recommends that policymakers, academics, opinion leaders and educational administrators should consider seriously the desirability of the rescue of the educational sector from the decay. Keywords Decay, education, challenge, stakeholders and Nigeria